A case of Pasteurella multocida pneumonia needed to differentiate from non-tuberculous mycobacteriosis. (2018) - Itoh, Naoya; Kurai, Hanako
Abstract: We report a case of Pasteurella multocida pneumonia. A 71-year old Japanese woman with pulmonary infiltration of the lingual division of left lung 3 years before, which was thought to be caused by non-tuberculous mycobacteriosis (NTM) was referred to our clinic on account of chronic cough, sputum, dyspnea, and left pulmonary infiltration. Although she owned over 10 cats, no bites or scratches were mentioned. Pasteurella multocida was confirmed by the culture of the patient's bronchoalveolar lavage (BAL) fluid. NTM infection was ruled out by acid-fast bacillus smears, cultures, and polymerase chain reaction of three sputum specimens and BAL fluid. The infection route in this case was considered to have resulted from inhalation of contaminated aerosols or contact with her cats. Close contact with animals should be avoided, particularly for patients with chronic pulmonary diseases, as it is a risk factor for pneumonia due to Pasteurella multocida .